Growth and Production of Romaine Lettuce (Lactuca sativa L.) on Several Dosage of Rabbit Urine - Isnainy, Dony Rachim; Manurung, Adinda Nurul Huda; Asnur, Paranita; Kanny, Putri Irene (International Journal on Food, Agriculture and Natural Resources, 2024)
Romaine lettuce is a vegetable with high economic value. Romaine lettuce needs to be grown organically. This research aimed to study the effect of various doses of rabbit urine on romaine lettuce. This research was conducted from June to August 2022 at the Smart and Urban Farming Laboratory Greenhouse, Campus F7, Gunadarma University, East Jakarta, Indonesia. The study used a randomized block design (RBD) with five replications, consisting of 5 treatments, namely: P0: without rabbit urine (control); P1: Concentration of rabbit urine 25%; P2: Concentration of rabbit urine 50%; P3: Concentration of rabbit urine 75%; P4: Concentration of rabbit urine 100%. The results showed that the administration of rabbit urine had no significant effect on the growth and yield of romaine lettuce plants, and the best concentration of rabbit urine for romaine lettuce plants in this study was 80 ml (P2).